Mockery, Populism and The Textual Devaluation of Humanities Research on Twitter - Annisa Nur Rahma; Elysa Hartati (International Journal of Science and Environment (IJSE), 2026)
Digital platforms have increasingly become arenas for cyber anti-intellectualism, where academic expertise is actively devalued by the public. This study investigates the linguistic construction of this hostility through a case study of the viral backlash against Dr. Ally Louk on Twitter (X). Employing Fairclough’s three-dimensional Critical Discourse Analysis (CDA), the research analyzes a corpus of 50-high-engagement replies to identify how anti-intellectual sentiment is textually produced and socially legitimized. The findings reveal that this backlash was not a series of random insults but a structured ideological performance driven by five discursive strategies, predominantly Hostile Populist Rhetoric (48%) and Mockery (46%). The analysis demonstrates that these strategies function to enforce a “market audit” on higher education, where a potent alliance of neoliberal rationality and cultural populism delegitimizes humanities research as economically “wasteful”. Furthermore, the study uncovers a distinct gendered dimension, where patriarchal norms are weaponized to reframe female intellectual labor as socially deviant. The study concludes that digital anti-intellectualism is infrastructurally amplified by platform affordances, underscoring the urgent need to shift the narrative of higher education from economic utility to civic necessity to counter the algorithmic amplification of populist resentment.